Prediction and control for the transmission of brucellosis in inner Mongolia, China - Sijia Liu; Jiajing Hu; Yifan Zhao; Xinyan Wang; Xuemei Wang (Scientific Reports)
Abstract Brucellosis, a zoonotic infectious disease caused by the Brucella genus, remains a significant global public health concern, with Inner Mongolia, China, being a notable hotspot affecting both human health and livestock. In response to this, we developed a dynamic SEIVWS h I ah I ch model to simulate the transmission of brucellosis in Inner Mongolia. We calculated the basic reproduction number (R 0 = 2.86), indicating a severe epidemic trend with cases expected to increase over the coming decades. The model was fitted to human brucellosis data, and key transmission parameters were estimated to predict future trends. We also evaluated the impact of various control measures, including vaccination, disinfection, culling, and health education. While these measures positively influence disease control, they cannot completely eliminate brucellosis, suggesting that a single control strategy is insufficient. Combining vaccination and culling proved more effective, with identified threshold values for R 0 and to keep R 0 < 1. Our findings indicate that a comprehensive strategy integrating vaccination, culling, disinfection, and health education is essential for effectively curbing brucellosis in Inner Mongolia, providing a strong foundation for optimizing future prevention and control strategies.